The Influence of Understanding The Accountant Profesional Code of Ethics On Students - Tahaku, Nur Diyanti; Leofandy, Faidz; J, Juwita; Panto, Natasya Yuliana; Budiawan, Shella (Amsir Accounting & Finance Journal, 2024)
This research discusses the important role of understanding the code of ethics in shaping the ethical behavior of accounting students. The code of ethics for the accounting profession, which includes aspects of integrity, objectivity, professional responsibility, public interest, professional competence, confidentiality, technical standards and professional behavior, is the main focus in guiding student behavior. However, there are challenges in implementing this code of ethics, such as a lack of understanding which gives rise to dishonest behavior during exams or quizzes. This raises concerns about the quality of behavior in the future when students enter the world of work as accountants. Apart from understanding the code of ethics, variables such as love of money (tendency towards money) and religiosity are also important highlights in shaping the behavior of accounting students. The research methods used include reviews of previous journals and data sources from Google search results, providing a comprehensive picture of the role of understanding the code of ethics in the context of accounting student behavior. This research aims to gain a deeper understanding of how ethics and understanding the code of ethics can shape professionalism among accounting students.